Effects of solid lubricant fillers on the flexural and shear strength response of carbon fabric-epoxy composites. (April 2021) - Rao, Yermal Shriraj; Mohan, Nanjangud Subbarao; Shetty, Nagaraja; Shivamurthy, Basavannadevaru
Abstract: Multi-layered carbon fabric-epoxy composites (CFEC) encounter certain challenges in expanding their usage mainly due to their low interlaminar shear strength (ILSS) and sensitivity to delamination damage. The present article focuses on evaluating the effectiveness of the fillers molybdenum disulfide (MoS2 ) and hexagonal boron nitride (h-BN) (2–8 wt%) on the flexural and the shear properties of the CFEC. The filler dispersion in epoxy resin is achieved by ultrasonication and composite fabrication through vacuum-assisted hand lay-up process. The filler surface area, evaluated as per nitrogen adsorption principles, reveals characteristics of hysteresis isotherm and mesoporous structure in both the fillers. Fourier transform infrared analyses on MoS2 reveal the stretch vibration due to molybdenum-sulfur and disulfide bonds whereas, in the h-BN, the transverse stretching and the out-of-plane bending happen due to boron-nitrogen and the boron-nitrogen-boron molecular group, respectively. Further analysis in the atomic force microscope shows more regular filler distribution at the outer surface for 4 and 6 wt% filler loaded CFEC whereas, 8 wt% filler loading results in an uneven particle distribution and attains the minimum surface roughness. The study exhibits the maximum ILSS (43.46 MPa) which is 43% enhancement compared to the neat CFEC for 6 wt% h-BN loaded CFEC. The maximum flexural strength (532 MPa) was noticed in 4 wt% MoS2 loaded CFEC signifying 62% improvement compared to the neat CFEC. The structural property improvements were witnessed because of the regularly distributed filler that strengthens the fiber-matrix interaction zone and reduces the matrix crack. The findings reveal that the proposed enhanced scheme by solid lubricant fillers proves to be more favorable for improving the matrix-dominated properties and the bending stiffness compared to the other particle-reinforced approaches. Graphical abstract: Image 1 Highlights: 4 wt% MoS2 -carbon fabric-epoxy composite exhibits better flexural strength, fiber-matrix interaction and crack deflection. 4 wt% h-BN-carbon fabric-epoxy composite showed better flexural modulus. 6 wt% h-BN-carbon fabric-epoxy composite showed better ILSS due to restriction of movement for layers in composite. More than 6 wt% filler causes stress raisers and deteriorates the ILSS and flexural properties. The matrix dominated properties improved by judicious quantity of MoS2 and h-BN filler in the composites.